Combination therapy of Fludarabine and Cyclophosphamide(FC) Combination Regimen in advance stage of Chronic Lymphocytic Leukemia - Matti, Bassam F.; Naji, Alaadin S.; Majid, Amar F.; Sabir, Shahlaa’ F.; Alwan, Alaa F. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: the exposure of chronic lymphocytic leukemia (CLL) cells to fludarabine and cyclophosphamide resulted in an increased, synergistic cytotoxicity . DNA repair mechanisms in CLL cells, which are initiated in response to cyclophosphamide exposition, are inhibited by fludarabine. This observation was later translated into clinical trials evaluating the combination of fludarabine plus cyclophosphamide (FC) showed promising efficacy with response rates exceeding 90% in previously untreated and pretreated patient Aim of this study: To assess the efficacy and safety of combination therapy of fludarabine plus cyclophosphamide in Iraqi adults patients with advance stage of chronic lymphocytic leukemia (CLL) in both previously treated and untreated patients and to assess the treatment free and overall survival in CLL patient who are receiving FC regimen therapy. Patients and methods: Single arm study was done between February 2005 and fabruary2009.This study included 64 Iraqi patients aged between 39-77years old with advanced stage CLL .All patients received FC combination Therapy(fludarabine25mg/m2 plus cyclophosphamide 250mg/m2 for 3 days intravenously, repeated every 28 days). Treatment was administered for 4-6 courses. Forty eight(75%) patients were treatment naive(N) and 16(25%)were previously treated(Y) with alkylating agent. Results: This combination chemotherapy resulted in 39.1% complete remission rate(CR) and 39.1%partial remission(PR) rate with overall response rated78.2%.The 2years median treatment-free survival was 90% with the median duration of response was 18months. Also there was a significant difference(p value <0.005) between different stage group(C&B) and degree of response, with better response rate in those with stage C than those with stage B, as the overall response rate was 88.3% and 65.5% respectively. By common toxicity criteria (CTC) grading, the major toxicity(grade 3-4) in patients who treated by FC regimen were nausea and vomiting while the myelosuppression was prominent complication of grade 1&2 as leucopenia and neutropenia occur in 19%, 14% respectively however this is not increased the number of severe infections. Conclusion: Fludarabine and cyclophosphamide combination regimen is an effective therapy for patients with advance CLL with high response and complete remission rate in those untreated and pretreated CLL patients, with good tolerability to this combination